2022
DOI: 10.1155/2022/3528915
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of High-Quality Nursing Service for the Patients during the Anesthesia Recovery Period: A Meta-Analysis

Abstract: Background. To investigate the efficacy of high-quality nursing service for the patients during the anesthesia recovery period. Methods. We used the National Library of Medicine (PubMed), Cochrane Library of Excerpta Medica Database (EMBASE), China National Knowledge Infrastructure (CNKI), Wanfang, and very important person (VIP) databases for conducting a systematic literature study. We employed the fixed-effects model for evaluating the standardized mean differences (SMDs) with 95% confidence intervals (CIs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%